The Initiation of a Young Plower – Between Myth and Reality. “First Turf” by M. Đ. Glišić in the Context of Oral Folklore and Traditional Culture of the Serbs - Perić, Dragoljub Ž.; Jokić, Jasmina S. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper aims to show how and to what extent the very archaic ritual complexes and beliefs appear in the considered Glišić’s story on the subtextual level (as a „hidden narrative”), related to the ritual cutting the first turf, as a kind of agrarian initiation of the young plowman. This semiotic interpretation conducted here was carried out at the level of analysis of space and time, actors, actions, communication, as well as the analysis of their accompanying elements (taboo regulations, ritual behavior, props, food and drink, etc.) related to the plowing the first furrow in the context of the ritual of maturation. Numerous and diverse ethnographic records of folk customs and ritual practices related to the (secondarily ritualized) cutting the first turf were used as material for comparison, in order to show how and to what extent Glišić, writing about life in the countryside, deeply knew and inherited our traditional culture, which was incorporated as the (often invisible) basis of author’s narrative world.
Keywords: traditional culture; ritual lyric; story; subtext of traditional; ritual plowing; initiation rite; change of social roles